Fuzzy Random Bimatrix Games Based on Possibility and Necessity Measures - Yano, Hitoshi (Journal of advanced computational intelligence and intelligent informatics, 2021)
In this study, we formulate bimatrix games with fuzzy random payoffs, and introduce equilibrium solution concepts based on possibility and necessity measures. It is assumed that each player has linear fuzzy goals for his/her payoff. To obtain equilibrium solutions based on the possibility and necessity measures, we propose two algorithms in which quadratic programming problems are solved repeatedly until equilibrium conditions are satisfied.